Availability of substances for use in personal vaporisers on three online cryptomarkets. (1st December 2020) - Lim, Carmen C.W; Leung, Janni K.Y; Connor, Jason P.; Hall, Wayne D.; Gartner, Coral; Cheng, Brandon H.C; Scheurer, Roman W.; Sun, Tianze; Chan, Gary C.K
Highlights: Cannabis oils containing THC were the most common substance advertised for use in a personal vaporiser. Synthetic cannabinoids and psychedelic substances were the next most common marketed substance. Future studies should continue to monitor cryptomarkets to identify emerging trends of substances used in personal vaporisers. Abstract: Background: Personal vaporisers are gaining popularity as an alternative route of administration for a range of substances. Online cryptomarkets are becoming increasingly popular among people who use substances due to their perceived anonymity, ease of use, and reduced risk of violence compared to traditional face-to-face dealers. We examined the diversity of substances marketed for use in a personal vaporiser on these marketplaces. Methods: Vaping related listings were extracted from three online cryptomarkets ('Agartha', 'Cryptonia', and 'Tochka') using The Onion Router browser. Data collection occurred between October and November 2019. Results: We identified 1929 listings from 201 unique sellers. The top product on Agartha, Cryptonia, and Tochka were vape cartridges prefilled with the e-liquid (70.4 %, 39.4 %, 52.3 % respectively). The most common substance in these products was cannabis oil (96.1 %, 82.1 %, 87.8 %), followed by synthetic cannabinoids (3.7 %, 9.7 %, 9.8 %) and psychedelic substances (0.2 %, 6.4 %, 1.2 %). Vendors were primarily from the USA. Many products offered worldwide shipping (96.3 %, 42.4 %, 51.2 %). Conclusion: Vaping products listed on online cryptomarkets in 2019 primarily contained cannabis oils. Future studies should continue to examine cryptomarkets to identify emerging trends of substances that can be used in personal vaporisers.